Voyage aux régions équinoxiales du nouveau continent, fait en 1799, 1800, 1801, 1802, 1803 et 1804 - Humboldt, Alexander von, 1769-1859. (Paris Paris Paris Paris Paris Paris Paris)
13 cilt (1. c. 439, [1] sayfa ; 2. c. 581, [1] sayfa ; 3. c. 381, [1] sayfa ; 4. c. 331, [4] sayfa, 69, [1] sayfa ; 5. c. 318 sayfa ; 6. c. 396 sayfa ; 7. c. viii, 455 sayfa ; 8. c. 526, [2] sayfa ; 9. c. 419 sayfa ; 10. c. 478 sayfa ; 11. c. 416 sayfa ; 12. c. 407 sayfa ; 13. c. 166 sayfa, [1] katlı tablo